'We Need Diverse E-Books:' Availability of Award-Winning Children's and Young Adult Titles in Today's E-Book Platforms. Issue 3 (25th March 2021) - Lear, Bernadette A.; Pritt, Andrea L.
Abstract: The COVID-19 pandemic has made librarians responsible for children's book collections in academic libraries acutely aware of the need to acquire children's and young adult materials in electronic formats. This research project compared the availability of 1, 600 award-winning and professionally-recognized PreK–12 titles within the e-book platforms of EBSCO, Follett, Hoopla, Mackin, Overdrive, ProQuest, and Tumblebooks. In addition, the authors examined the availability of children's e-books pertaining to racial/ethnic, gender, LGBTQ+, and disability diversity from these vendors. The results of this study indicated that there were substantial disparities in the availability of e-books by grade level and by publisher. The availability of titles pertaining to people of color, women, LGBTQ + persons, and people with disabilities was usually (but not always) similar or better compared to the availability of all titles in the dataset.